Did the exchange rate interventions enhance inflation in Switzerland? - Libor Žídek; Magdalena Šuterová (Kiel Institute for the World Economy (IfW), 2017)
For nearly five years, the Swiss National Bank intervened against the Swiss franc to prevent increase of deflation pressures. An unexpected switch in monetary policy was made in January 2015, and the regime was abandoned. In this paper, the authors examine the exchange rate influence on the inflation in Switzerland, separately for the pre-crisis and the intervention period. Using autoregressive models, they quantify the extent of pass-through of an exchange rate shock to different price indices. The results suggest that the exchange rate interventions did indeed enhance the exchange rate pass-through into inflation. Despite the effect's moderate influence, the decline was not immediate. The authors additionally analysed long-term exchange rate pass-through. The examination reveals that the long-term behaviour arises rather from the intervention than from the precrisis period. The exchange rate effect on inflation was thus in a better accordance with theory during the intervention period. As such, currency depreciation did have a positive effect on inflation in Switzerland.
Keywords: C32; E31; E52; 330; Swiss National Bank; exchange rate interventions; exchange rate passthrough; SVAR